New name for Progrillotia dollfusi Carvajal et Rego, 1983 (Cestoda: Trypanorhyncha): description of adults from Squatina guggenheim (Chondrichthyes: Squatiniformes) off the coast of Argentina - Menoret, Adriana; Ivanov, Verónica A (Folia parasitologica, 2009)
Examination of the type material of Progrillotia dollfusi Carvajal et Rego, 1983, and of new specimens recently collected off the coast of Argentina (including plerocerci from 10 species of teleosts and adults from Squatina guggenheim Marini), allowed a detailed redescription of this species and the evaluation of its current taxonomic status. The following characters that have been treated inconsistently by different authors have been herein corrected or confirmed: band of hooklets on external surface restricted to the base of the tentacle, external surface of metabasal region with 3-5 intercalary hooks arranged in a single row merging immediately to a cluster of 3-4 hooklets arranged in two rows; retractor muscle originating in the posterior third of the bulb, hollow hooks, and posterior margin of bothria notched. These features along with the presence of postovarian testes in the adults clearly confirm the placement of P. dollfusi in the genus Grillotia Guiart, 1927. In order to avoid the homonymy with Grillotia dollfusi Carvajal, 1971, a new name, Grillotia carvajalregorum nom. n., is proposed. This species differs from the 16 valid species in the genus in the combination of the following characters: number and morphology of hooks in principal rows in proximal metabasal region of the tentacle, number and distribution of intercalary hooks, presence of clusters of hooklets, extent of band of hooklets on external surface of basal armature, site of origin of the retractor muscle, and features of the terminal genitalia. The present study describes the plerocerci and adult worms, and provides detailed description of the microthrix pattern and histology of this species for the first time.
Keywords: Animals; Atlantský oceán; cestodózy; nemoci ryb; Cestode Infections; Sharks; zvířata; Atlantic Ocean; Fish Diseases; Cestoda; žraloci; Argentina